Value and contrarian investment strategies: Evidence from Indian stock market - Sharneet Singh Jagirdar; Pradeep Kumar Gupta (Journal of Risk and Financial Management, 2023)
Value and contrarian investment strategies are two basic approaches which are widely used by investors worldwide. Both value and contrarian investment strategies are assumed to pick the same stocks even though the approach to picking the stocks is different. Furthermore, both investment strategies are supposed to work in various forms of market efficiency. The present study aims to empirically review and analyze the investment strategies, value and contrarian, by creating a portfolio of returns of listed stocks in India's Bombay Stock Exchange (BSE) over a period from 1990-91 to 2018-19. A Venn diagram is used to explain the selection of stocks under both investment strategies with analysts' forecast recommendations. The findings show that value and contrarian investment strategies essentially select different stocks at any given point in time. Moreover, the study finds that both investment strategies can work in the same form of market efficiency. This study brings new insights to scholars, analysts, and investors for analyzing investment strategies and their portfolio composition.
Keywords: 650; analysts; contrarian stocks; investment strategy; market efficiency; value stocks